Development of a Rubric to Measure Radiography Programmatic Assessment Plan Quality. - Hamm, Rebecca G.; Hebert, Dustin M.; Allen, Tina; Whitlock, Dustin (Radiologic Science & Education, 2024)
This study proposes a self-assessment method for radiography program directors and instructors to develop and evaluate their programmatic assessment plans. There is a lack of training for those who contribute to radiography program assessment plans, often leading to citations by the Joint Review Committee on Education in Radiologic Technology. To address this issue, a compre- hensive rubric was developed and validated using the Delphi technique, engaging 20 experts with extensive knowledge and experience in radiography programmatic assessment. Consensus was achieved after three rounds of evaluation. Participant feedback during rubric testing underscored the rubric's relevance and usefulness while also suggesting areas for further refinement in its devel- opment. This study provides a valuable tool for improving the quality of radiography program- matic assessment plans and contributes to the enhancement of educational standards in radiologic technology education.